The Reception of the Gospel of John in the Long Recension of Ignatius’s Letters - Lookadoo, Jonathon (Journal for the study of the New Testament, 2020)
The reception of Pauline and Johannine writings in the three centuries after their composition is of interest to NT researchers, and Ignatius of Antioch’s letters have rightly been taken into consideration when studying NT reception history. This article aims to fill a lacuna in reception historical studies of Ignatius’s epistles by exploring the role of John’s gospel in the fourth-century long recension. The long recension employs John when discussing Christology, Trinity, unity, Jewish-Christian identity, resurrection and for polemical purposes. This article thus contributes to ongoing reception historical studies of the NT within Ignatian literature, examines how the Gospel of John was employed by a fourth-century author and explores ways in which John is utilized to expand, update and modify the Ignatian middle recension.